KAJIAN SOSIAL-BUDAYA MASYARAKAT PADA LANSKAP RIPARIAN SUNGAI CILIWUNG - Fittria Ulfah; . Nurhayati; Hadi Susilo Arifin (http://arl.faperta.ipb.ac.id/, 2017)
Bogor as one of the cities with high population density located in the middle of Ciliwung watershed. The use of riparian rivers as undeveloped land has had an impact on the decline in the quality and quantity of blue open spaces. The factors that most influence riparian landscape change are the interaction between human activity and the landscape associated with socio-cultural activities. The purpose of this study was to analyze the situational and sociocultural activities of riparian Ciliwung River to blue open space. This conducted in the city of Bogor that is on Pulo Geulis and Griya Katulampa. The method that used in this research is descriptive analysis where the data analyzed is obtained from interview and literature study. The results of this study indicate the existence of two socio-cultural interactions in two research sites, in Pulo Geulis settlement and Griya Katulampa Housing with situational condition of riparian landscape which is relatively the same. The difference results of between community interactions with the landscape is strongly influenced by the background of the local community.